Production of Functional Kampong Chicken Meat with Low Cholesterol, High Antioxidant, and Unsaturated Fatty Acids Fed Noni (Morinda citrifolia) Leaf Shoot Meal - Wardiny, T. M.; Sumiati, Sumiati; Retnani, Y.; Setiyono, A. (Tropical Animal Science Journal, 2020)
The objective of this study was to evaluate the effect of noni (Morinda citrifolia) leaf shoot meal (NLSM) supplementation in the ration on the performances of kampong chickens as well as lipid, malondialdehyde (MDA), and fatty acid contents of meats. Two hundred and forty kampong chickens of 4 weeks old were reared until 12 weeks old. The diet treatments were R0: 0% NLSM (control), R1: 0.5% NLSM, R2: 1% NLSM, R3: 1.5% NLSM, R4: 2% NLSM, and R5: 2.5% NLSM. A completely randomized design (CRD) was used with six treatments and four replications with ten kampong chickens per replicate. The data were analyzed using ANOVA and if there were significant different, the data were further analyzed using Duncan’s Multiple Range Test. The variables measured were performances of kampong chickens as well as lipid, MDA, and fatty acid contents of meat. The result showed that cholesterol and LDL contents of meat were significantly reduced by feeding NLSM. Performance and HDL contents of meat were not significantly different for all diet treatments. In addition, feeding kampong chickens with ration supplemented with NLSM could reduce MDA, saturated fatty acids and increase unsaturated fatty acids contents of meat. It is concluded that 2.5% NLSM can be used to improve meat quality of kampong chicken as functional meat.